Analisis Putusan Mahkamah Konstitusi Nomor 65/PUU-XXI/2023 tentang Kampanye di Ranah Pendidikan dalam Perspektif Hak Asasi Manusia - Didi Nazmi (UNES Law Review, 2023)
Elections are instruments or means to carry out democracy, even in many democratic countries, elections are considered as a symbol as well as a benchmark for democracy. In the implementation of people's sovereign participation, namely elections, of course, a mechanism or flow of implementation is needed to minimize the violation of democratic values. In terms of limitations in organizing campaigns, justice is a very important thing in the political process. Recently, there was a Constitutional Court Decision Number 65/PUU-XXI/2023 against a request for legal uncertainty regarding the Explanation in Article 280 paragraph (1) letter h of Law Number 7 of 2017 Concerning General Elections. This legal uncertainty is caused by contradictions between norms and explanations, causing chaos in the field. This research is a legal research (doctrinal research) with a conceptual approach (conceptual approach), statutory approach (statues approach) and case approach (cases approach). The results of this study explain first, campaign arrangements in Indonesia regulate methods, materials, to the vision and mission and programs that will be conveyed by election participants to prospective voters based on the principle of fairness in holding elections. Second, the prohibition of campaigning in the education sector is part of the derogable rights of the right to express opinions. The Court still maintains the provisions prohibiting campaigning through educational places by placing the phrase exceptions still needed to be contained in the body of Law 7/2017 as a separate norm to create legal certainty.